New/emerging psychoactive substances and associated psychopathological consequences. Issue 1 (22nd January 2021) - Schifano, F.; Napoletano, F.; Chiappini, S.; Guirguis, A.; Corkery, J. M.; Bonaccorso, S.; Ricciardi, A.; Scherbaum, N.; Vento, A.
Abstract: Background: The present paper provides an updated review of both the large number of new/novel/emerging psychoactive substances (NPS) and their associated psychopathological consequences. Focus was here given on identification of those NPS being commented in specialised online sources and the related short-/long-term psychopathological and medical ill-health effects. Methods: NPS have been identified through an innovative crawling/navigating software, called the 'NPS.Finder®', created in order to facilitate the process of early recognition of NPS online. A range of information regarding NPS, including chemical and street names; chemical formula; three-dimensional image and anecdotally reported clinical/psychoactive effects, were here made available. Results: Using the 'NPS.Finder®' approach, a few thousand NPS were here preliminarily identified, a number which is about 4-fold higher than those figures suggested by European and international drug agencies. NPS most commonly associated with the onset of psychopathological consequences included here synthetic cannabinoids/cannabimimetics; new synthetic opioids; ketamine-like dissociatives; novel stimulants; novel psychedelics and several prescription and over-the-counter medicines. Conclusions: The ever-increasing changes in terms of recreational psychotropics' availability represent a relatively new challenge for psychiatry, as the pharmacodynamics and pharmacokinetics of many NPS have not been thoroughly understood. Health/mental health professionals should be informed about the range of NPS; their intake modalities; their psychoactive sought-after effects; the idiosyncratic psychotropics' combinations and finally, their medical and psychopathological risks.